A multi-dimensional analysis of managers' power: Functional, socio-political, interpretive-discursive, and socio-cultural approaches - Thomas Diefenbach; Rune Todnem By; Patricia Klarner (Management Revue, 2009)
Managers' power within organisations has been analysed by several approaches: Orthodox management and organisation studies ('functional approach'), Critical Management Studies ('socio-political approaches'), interpretive, discourse-oriented and constructivist concepts ('interpretive-discursive approaches'), and anthropological, socio-psychological and sociological approaches ('socio-cultural approaches'). In organisational reality functional, socio-political, interpretive-discursive, and socio-cultural aspects are closely related and intertwined. However, because of division of intellectual labour, probably more because of different worldviews, researchers often make use of these approaches quite selectively. Such focussing has its advantages but also weaknesses. This paper therefore argues that it often helps to investigate complex phenomena such as managers' power in multi-dimensional ways.
Keywords: 650; power; managers; management studies; organisation